Person Centeres Surgery - Haro-Haro, Daniel Enrique (2021)
This work aims to make a review of the person-centered surgery, the historical background, the basic principles of the surgical practice, and the profile of the humanist and humanitarian surgeon. It prioritizes the bond with the patient and the goals to be achieved in the curricular plans of surgeon training, and analyzed the importance of informed consent in surgery. The authors make a proposal to improve its effectiveness, emphasizing that, at all times, surgeons must accept with honesty and ethics, essential requirements for a good professional practice, offering his ability for the benefit of the patient.